Determination of the electrical characteristics and thermal behaviour of a c-Si cell under transient conditions for various concentration ratios. Issue 9 (20th October 2016) - Kaplanis, S.
Abstract : An extended study of c-Si cell performance under transient conditions for various concentration ratios, C, between 0.6 and 12.25 is presented. PV cell temperature, T c, open-circuit voltage, V oc, and short-circuit current, I sc, were measured using an experimental set-up based on a solar light simulator. The dependence of V oc, I sc, d V oc /d T c, d I sc /d T c and r s on T c was investigated against C . A model was developed to predict T c . Generalised formulae were proposed for prediction of V oc and I sc . Theoretically obtained T c and V oc profiles were compared with the measured ones. A good agreement was observed. The time constants of V oc and T c profiles were determined experimentally for various C values and lie within ±5% from theoretically predicted time constants. The coefficient d V oc /d T c was determined for various C values. The results show a decrease in the absolute value of d V oc /d T c against C . A partial recovery of PV cell performance through a ventilation process was tried.